Tecnologias de informação: sua influência no aprimoramento do acesso à informação e democratização do conhecimento - Gonçalves, Eliane Silveira (2012)
This paper discusses, from literary analysis and Focus Group interviews through the influence of information technology in information access and democratization of knowledge. The innovations that have occurred around the world show that the technologies in general have influenced the daily life of the individual causing a decrease in distance of the users of the information and knowledge. This distance has been affected with the help of the tools of Information Technology that is now present worldwide through numerous tools such as scanners, computers, internet, scanning, among others. For this study we used only the Internet and scanning tools, which are now largely responsible for changes in existing information age, which has influenced access to information and the democratization of knowledge. What we see through this research is that access to information today is not just on access but also contribute to intervene and disseminate information that is produced. Moreover, with technological innovations can consider the possibility of a democratization of knowledge not only in the world and in Brazil. To achieve this research was used to produce literature by authors in the field of Information Technology, Information and Knowledge, and to help in this work we also used interviews with ten professionals who work with information technology and users who use these tools for their daily activities